Optimal control of continuous dynamics programming processes in the infinite interval of time - Bistrickas, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Бистрицкас. Оптимальное управление непрерывным процессом динамического программирования в бесконечном интервале времениV. Bistrickas. Optimalus tolydinio dinaminio programavimo proceso valdymas begaliniame laiko intervale